Optimalisasi digital marketing bagi UMKM: Pelatihan digital marketing dan strategi konten di sosial media - Setiyawan, Ayuk; Erikawati, Civi; Mumtaz, Lutfiyah; Susilowati, Eny (Nur Science Institute, 2025)
This community service activity aims to enhance the knowledge and skills of members of the 'Aisyiyah Entrepreneurship School (SWA) in Karanganyar in digital marketing and social media content strategy. The program was motivated by the low level of digital literacy and limited use of digital platforms among MSME actors. The method employed was structured training, comprising lectures, discussions, and hands-on practice, as well as registering as affiliates on e-commerce platforms. The participants included 30 SWA members who are actively engaged in micro-businesses. The results showed a significant improvement in participants' understanding and involvement in applying digital marketing strategies, as well as utilizing social media and affiliate tools for product promotion. The enthusiasm was reflected in the high participation during both the discussion and practical sessions. This activity made a positive contribution by promoting digital transformation among local MSMEs and increasing their competitiveness in the digital economy era.